Under the sun: adaptation effects to changes in facial complexion - Sandra Utz; Ronja Mueller; Tilo Strobach; Claus-Christian Carbon (BMC Psychology, 2023)
Abstract Background Many Western people enjoy sunshine, and through the sun’s stimulated increase in melanin, the skin tone or skin complexion will darken (and lighten again during winter). Although the initial salience of such a new look is remarkable – especially in the face – we seem to adapt to this new look relatively quickly. Research on face adaptation in general repeatedly showed that the inspection of manipulated versions of faces (so-called adaptor faces) leads to a change of the perception of subsequently presented faces. The present study investigates face adaptation to very natural changes in faces such as changes in complexion. Methods During the adaptation phase in the present study, participants saw faces with either strongly increased or decreased complexion. After a pause of 5 min, participants had to identify the veridical (non-manipulated) face out of two faces (a face slightly manipulated in complexion combined with the non-manipulated face) during a test phase. Results Results show strong adaptation effects to decreased complexion intensities. Discussion It seems that we are updating our facial representations in memory quite quickly (i.e., optimizing our processing through adaptation) and seem to sustain those new representations over a certain timespan (at least 5 min). Our results demonstrate that changes in complexion draw our attention for deeper analysis (at least with decreased complexion). However, it loses its informative quality quickly via fast and relatively sustainable adaptation.